2009
DOI: 10.1007/s10479-009-0596-2
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid scatter tabu search for unconstrained global optimization

Abstract: The problem of finding a global optimum of an unconstrained multimodal function has been the subject of intensive study in recent years, giving rise to valuable advances in solution methods. We examine this problem within the framework of adaptive memory programming (AMP), focusing particularly on AMP strategies that derive from an integration of Scatter Search and Tabu Search. Computational comparisons involving 16 leading methods for multimodal function optimization, performed on a testbed of 64 problems wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 32 publications
0
32
0
14
Order By: Relevance
“…We point out that, similar procedures based on design of experiments have been used in the literature to generate populations of diverse solutions. See for instance the implementations in , (Duarte, Glover, Martí, & Gortázar, 2011) and The solutions in are evaluated by calling the black box. That is, the objective function value and feasibility of the solutions are known for each solution .…”
Section: Diversification Generation Methodsmentioning
confidence: 99%
“…We point out that, similar procedures based on design of experiments have been used in the literature to generate populations of diverse solutions. See for instance the implementations in , (Duarte, Glover, Martí, & Gortázar, 2011) and The solutions in are evaluated by calling the black box. That is, the objective function value and feasibility of the solutions are known for each solution .…”
Section: Diversification Generation Methodsmentioning
confidence: 99%
“…Tabu search (TS) is a well-known meta-heuristic (Glover, 1989;Glover, 1990) which has proven to be effective for solving a large number of practical optimization problems, including quadratic assignment (James et al, 2009), unconstrained global optimization (Duarte et al, 2011), course timetabling (Lü and Hao, 2010), graph coloring (Wu and Hao, 2012), etc. For CODP, this paper employs a TS procedure as follows.…”
Section: Tabu Search Proceduresmentioning
confidence: 99%
“…Yin et al (2010) have shown the advantages of the original CyberSA by comparing it with several other metaheuristics such as the Standard PSO 2007 (Clerc, 2008), C-GRASP (Hirsch et al, 2007), Direct Tabu Search (Hedar & Fukushima, 2006), Scatter Search (Laguna & Marti, 2005), and Hybrid Scatter Tabu Search (Duarte et al, 2011a). In our present comparison we also include the PSwarm algorithm of Vaz and Vicente (2007), which embeds the swarm algorithm into the pattern search framework.…”
Section: Performance Measures and Competing Algorithmsmentioning
confidence: 99%